ChatGPT and the Future of Health Policy Analysis: Potential and Pitfalls of Using ChatGPT in Policymaking - Sifat, Ridwan Islam (Springer Nature, 2023)
Scholars increasingly rely on new artificial intelligence models for convenience and simple access to necessities due to the rapid evolution of scientific literature and technology. The invention of ChatGPT by OpenAI stands out as a key example of how significant advances in large language model technology have recently changed the field of artificial intelligence (AI). Since ChatGPT’s development, it has been tested by multiple sectors on various topics to see how well it functions in a natural and conversational mode. The crucial question is how much ChatGPT can influence global health policy analysis. In this article, the researcher briefly explains ChatGPT’s potential and the difficulties that users, such as researchers or policymakers, may continue to face.